Analyzing the impacts of climate change on farmers' livelihood in the center of Vietnam : case study in Nui Thanh District, Quang Nam Province - Pham Thi Ly; Shivakoti, Ganesh P.; Nguyen, Thi Kim Oanh; Jourdain, Damien; Mai Trong Thong; Government of Denmark (DANIDA); Asian Institute of Technology Fellowship (Pathum Thani : Asian Institute of Technology, 2012)
In recent years, climate changehas becomea big problemindeveloping countries all overthe world, especially in Vietnam. The study about the impacts of climate change on farmer{u2019}slivelihood is notconducted atlocal scaleinVietnam. This studyanalysesthe impacts ofclimate change on agricultural livelihoodsin Nui Thanh district-a coastal district of centralVietnam wheresomany natural disastershitannually.This study persued to seek followingqueries including the trends in climatic factors, their effects on agriculture livelihood oflocal farmers, impactson agriculture productivity as perceived by the farmers on theirlivelihood, and their adaptive measures to climate change.First,this study found out thetrendsinincrease of some climate factors such as average annual temperature, maximumaverageetemperature, total of annual rainfall and so on but the changes are not much. Thesechanges have affected significantly on agriculture livelihood of local farmers. With otherfactors, these changes contribute to reduce productivity and quality of agriculture products.The farmers have perceivedabout local climate change and impacts of changes to theirlivelihood in part closely to analysis from secondary data. Thus, with direction of localgovernment, they applied some measures to adapt to climate change and at first perceptionexpected outcome. However, due toclimate are more unstable in some recent years, income from agriculture islow and the households that with agriculture is main livelihood areusually poor.In order to reduce uncertainties from climate change, some activities aresuggested by authority, such as water storage and augmentation, mangrove forest plantation,developing adaptive suitable varieties, agriculture practice and regular training should becarried out.
A thesis submitted in partial fulfillment of the requirements fo rthe degree of Master of Science in Natural Resources Management, School of Environment, Resources and Development
Thesis (M. Sc.) - Asian Institute of Technology, 2012
Keywords: Farmers -- Vietnam -- Quang Nam; Climatic changes -- Vietnam -- Quang Nam